(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
World politics is entering a new phase, in which the great divisions among humankind and the dominating source of international conflict will be cultural Civilizations-the highest cultural groupings of people-are differentiated from each other by religion, history, language and tradition. These divisions are deep and increasing in importance. In this context the economic cooperation is the only way to achieve unity and somehow the equal growth and to provide quality of life to reduce these gaps effectively. Economic cooperation will lead the world towards peace and growth.Paradigmatic shift in India’s regional policy can be explained by post–cold war global political-economic developments. Indian leaders well know that the success of their country’s economic liberalization depends upon its ability to increase exports to new markets in developed and developing countries. Until recently, India has achieved only restricted access to the markets of Japan, North America, and Western Europe due to these countries’ projectionist policies and various kinds of non-tariff barriers against Indian products. Additionally, with the collapse of the Soviet Union and the gradual incorporation of Eastern Europe with, the west European economy, India has lost two of its privileged marked links. India’s growing interest in Central Asia is not confined merely to the linked threats of terrorism separatism, drug trading, and incitement to civil violence. It also has deep and long standing strategic and economic roots.